Front Cover: Spectrally encoded coherence tomography and reflectometry: Simultaneous en face and cross‐sectional imaging at 2 gigapixels per second (J. Biophotonics 4/2018). Issue 4 (17th April 2018) - El‐Haddad, Mohamed T.; Bozic, Ivan; Tao, Yuankai K.
Abstract : SECTR is a novel multimodal imaging platform for combined volumetric optical coherence tomography (OCT) and en face spectrally encoded reflectometry (SER). The authors demonstrate three‐dimensional motion‐tracking with millisecond temporal and micron spatial resolution using complementary data from OCT and SER, and preliminary algorithms and results showing real‐time image aiming and multi‐volumetric mosaicking for reconstruction of wide‐field composites. The image shows a noninvasively imaged nine‐field mosaic of in vivo human retina and depth‐resolved visualization of tissue microstructures. Further details can be found in the article by Mohamed T. El‐Haddad, Ivan Bozic, and Yuankai K. Tao (e201700268 ) Abstract : SECTR is a novel multimodal imaging platform for combined volumetric optical coherence tomography (OCT) and en face spectrally encoded reflectometry (SER). The authors demonstrate three‐dimensional motion‐tracking with millisecond temporal and micron spatial resolution using complementary data from OCT and SER, and preliminary algorithms and results showing real‐time image aiming and multi‐volumetric mosaicking for reconstruction of wide‐field composites. The image shows a noninvasively imaged nine‐field mosaic of in vivo human retina and depth‐resolved visualization of tissue microstructures. Further details can be found in the article by Mohamed T. El‐Haddad, Ivan Bozic, and Yuankai K. Tao (e201700268 )